1999
DOI: 10.1002/(sici)1096-9071(199909)59:1<122::aid-jmv20>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Poliovirus infection induces apoptosis in CaCo-2 cells

Abstract: The effects of poliovirus infection in CaCo-2 cells, a human enterocyte-like cell line are described. Infected cells were examined by a combination of techniques, including optical and electron microscopy, cytofluorimetric analysis of DNA content, and DNA agarose gel electrophoresis. Results obtained by the different experimental approaches demonstrate that poliovirus infection in enterocyte-like cells can result in an apoptotic process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…In our study of coxsackievirus B and poliovirus infected cell cultures, apoptosis of supernatant cells was complete at 4 h. This is consonant with the findings by other authors of apoptosis early in the viral replication of poliovirus [15] and coxsackievirus B infected cells [16]. We observed that virus replication in infected cell cultures took place in both the nuclei and cytoplasm.…”
Section: Discussionsupporting
confidence: 92%
“…In our study of coxsackievirus B and poliovirus infected cell cultures, apoptosis of supernatant cells was complete at 4 h. This is consonant with the findings by other authors of apoptosis early in the viral replication of poliovirus [15] and coxsackievirus B infected cells [16]. We observed that virus replication in infected cell cultures took place in both the nuclei and cytoplasm.…”
Section: Discussionsupporting
confidence: 92%
“…Results from these experiments demonstrated that, as reported for some other non-enveloped viruses [18][19][20][21][22][23][24][25], bLf prevents viral cytopathic effect. Enteroviruses are highly cytopathic and it has been reported that viral infection can induce two distinct pathways of cell death: necrosis and apoptosis [29][30][31]. Although some viruses have developed different ways to suppress apoptosis, several viruses trigger apoptosis in host cells at the late stage of infection probably to spread viral progeny [32].…”
Section: Discussionsupporting
confidence: 92%
“…In our experimental conditions, we demonstrated that echovirus infection mainly induces apoptosis. These results are in agreement with those reported for poliovirus and coxsackievirus B [31,33]. Moreover, exploring the possibility of an antiapoptotic activity of bLf in virus-infected cells, we demonstrated that this protein prevents both cell death and viral replication.…”
Section: Discussionmentioning
confidence: 97%
“…PV-induced motor neuron death was recently found to be mediated through an apoptotic process 3234 . PV was also reported to induce apoptosis in vitro in other cell types, including CaCo-2 colon cancer cell line 35 , U937 promonocytic cell line 36 , dendritic cells and macrophages 37 , and HeLa cells 38, 39 . However, the mechanisms by which PV induces apoptosis are not totally clear.…”
Section: Discussionmentioning
confidence: 97%